The STUDY OF SOLID WASTE AND ANALYSIS OF LOCAL PARTICIPATION IN LARANTUKA CITY OF EAST FLORES REGENCY - Anandra, Ajeng; Suarna, I Wayan; Sudarma, Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2018)
Larantuka is the capital of East Flores Regency, which  located in the most eastern part of Flores island and wellknown for its natural beauty. Despite  the tourism potentiontial, the development of infrastructure is not sufficient, especially in solid waste management. Larantuka city itself doesn’t have  a proper sanitary landfill facility, no recycle center and dizorganized management. This situation can be harmful for environment and the natural beauty of East Flores. The purpose of this study is to understand the waste management situation at the moment in East Flores District, how much waste that is produce everyday by all the activities and also the willingness of the people of  Larantuka to participate in waste management. The result of this study shown that 60 % of the resident in Larantuka is dissatisfied of their neighbourhood environment because of the lack of waste mangement. The result of the survey Larantuka produce  is 98 m 3 per day, that consist of 60 m 3 of organic matters, 17 m 3 of plastic, and 15,3m 3 of paper and others. Reduce, Reuse and Recycle are one of solution from this problems, but it needs cooperation between the residence, government and even private companies. Based on the  questionaire 57 % of the residence in East Flores still does not understand what 3R or Reduce, Reuse and Recycle as a solution to overcome the problem. Keywords : Community participation; Solid waste; Larantuka;  3R